Evidence Based Medicine: Principles and application to bipolar disorder - Goodwin, G (2005)
The author indicates what are the basic principles of Evidence Based Medicine, underlining its interest in terms of ethics, but also some of its limitations. As an example, he shows how EBM has led to the definition of therapeutic guidelines in the field of Bipolar Disorder, by the British Association for Psychopharmacology.